EFEKTIVITAS IMPLEMENTASI PERMENDAGRI 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA PADA PEMERINTAH DESA (Studi Kasus di Desa Pematang Sukaramah Kecamatan Mesuji Makmur Kabupaten Ogan Komering Ilir) - Lis Fatmawati (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
This study is aimed to know and assess whether the village finance management in Pematang Sukaramah Village Mesuji Makmur subdistrict Ogan Komering Ilir Regency has been implemented based on PEMENDAGRI Number 113 year 2014 or not. The data analysis technique in this study is descriptive analysis by using qualitative that are describing entirely and real concerning in village finance management in Pematang Sukaramah Village Mesuji Makmur subdistrict Ogan Komering Ilir regency. Village finance management are all the activities starting from planning and budgeting, implementation, structuring, reporting and responsibility. Based on the analysis and evaluation result had been done, can be concluded that PERMENDAGRI number 113 year 2014 in Village Government Pematang Sukaramah Village Mesuji Makmur subdistrict Ogan Komering Ilir Regency has been implemented but has not effective yet because there still some activities which done not based on the rule.